Implementasi Algoritma Elias Gamma Code Untuk Kompresi File Audio Hasil Rekaman Dari Aplikasi Wesing Karaoke - Redita Manik (STMIK Budi Darma, 2022)
In an era of increasingly sophisticated technology, such as today, the high activity of data storage and transmission creates a problem which can lead to wasteful storage space and slow data transmission processes online or offline. The longer data storage will result in accumulating more and more data. This data accumulation becomes a problem, especially from the availability of storage space. Along with current technological developments, the ability to process data is increasingly developing, namely by utilizing compression methods which are expected to answer these problems. The Elias Gamma Code algorithm is used to compress audio files recorded from the Wesing Karaoke application by reducing the file size from the beginning. So that by applying the Elias Gamma Code algorithm to compress audio files, it can reduce the optimal storage capacity on smartphones (cellphones).